Breton’s Wall, Carrington’s Kitchen: Surrealism and the Archive - Eburne, Jonathan (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2011)
Contemporary thinking about archives remains bound up in the vexed relationship between the political and the knowable. This essay explores the political epistemology of archives and archival practices, seeking to dislodge the contemporary scholarly discourse on archives from its tendency to instrumentalize archivation as either a repository of knowledge or an apparatus of power. In studying the collections of two members of the surrealist movement, this essay examines the extent to which archival practices instead suspend the certainties of political desire, disclosing the persistence of discontinuity within the closed systems into which such certainties always threaten to develop. It focuses on two archival collections: the studio of André Breton at 42, rue Fontaine in Paris, and the figural “kitchen” of Leonora Carrington's paintings and writings.